2014
DOI: 10.5664/jcsm.4024
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Clinical Significance of Supine-Dependent Obstructive Sleep Apnea in Patients Using Oral Appliance Therapy

Abstract: Study Objective: The prevalence of supine-dependent obstructive sleep apnea (sdOSA) in a general population ranges from 20% to 60%, depending on the criteria used. Currently, the prevalence and evolution of sdOSA once oral appliance therapy with a mandibular advancement device (OA m ) has started is unknown. In addition, literature on the correlation between sdOSA and treatment success with OA m is not unequivocal. The fi rst purpose of this study was to assess the prevalence of sdOSA before and under OA m the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 40 publications
2
27
0
1
Order By: Relevance
“…According to this defi nition, 46 % of patients were diagnosed as having sdOSA. Applying the same defi nition, Dieltjens et al [ 28 ] found a comparable prevalence of 46 % prior to the start of the OA m therapy. In three studies, the prevalence of sdOSA as defi ned by Cartwright's criteria was assessed before starting OA m therapy and ranged from 58 to 80 % [ 21 , 22 , 28 ].…”
Section: Prevalence Of Supine-dependent Sleep Apnea Under Oral Appliamentioning
confidence: 97%
See 2 more Smart Citations
“…According to this defi nition, 46 % of patients were diagnosed as having sdOSA. Applying the same defi nition, Dieltjens et al [ 28 ] found a comparable prevalence of 46 % prior to the start of the OA m therapy. In three studies, the prevalence of sdOSA as defi ned by Cartwright's criteria was assessed before starting OA m therapy and ranged from 58 to 80 % [ 21 , 22 , 28 ].…”
Section: Prevalence Of Supine-dependent Sleep Apnea Under Oral Appliamentioning
confidence: 97%
“…In a recent study 183 patients with polysomnographic data before and under OA m therapy were evaluated showing a prevalence under OA m therapy ranging from 18 to 34 %, depending on the defi nition used. In addition, it was shown that up to one third of patients shift from non-sdOSA at baseline to sdOSA under OA m therapy [ 28 ].…”
Section: -35 27mentioning
confidence: 99%
See 1 more Smart Citation
“…88 It may be attributable to unfavorable upper airway anatomy, reduced lung volume, and inability of airway dilator muscles to compensate for the airway collapse in the supine position.…”
Section: Endotypes and Phenotypes Of Osamentioning
confidence: 99%
“…Apart from the exploration of more effective titration procedures and an enhanced upfront prediction of individual patients' responses to MRD therapy, this efficacy might also be improved by a more accurate documentation of the reasons for any residual OSA under MRD therapy. Among others, there is recent evidence that a residual positional OSA is common as a reason for an incomplete elimination of OSA during MRD therapy [22]. In part, these findings can be explained by the fact that positional or supine-dependent OSA is much more common in patients with mild disease as compared to patients with a higher OSA severity at baseline [23].…”
mentioning
confidence: 97%